Influence of hatch spacing on molten pool evolution, defects generation and mechanical properties of SLM fabricated diamond/CuSn20 composites - Yangli Xu; Yu Sun; Guoqin Huang; Tingting Li; Haoqing Li; Weihong Wu; Xipeng Xu; Hidetoshi Saitoh (Journal of Materials Research and Technology)
Selective laser melting (SLM) is considered an effective technology in fabricating high-performance metal-bonded diamond tools with integrated internal cooling and chip evacuation channels. However, the formation of certain defects during the SLM process significantly compromises the mechanical properties and service life of diamond tools. Defect generation exhibits a strong correlation with laser processing parameters, among which laser hatch spacing constitutes a critical factor governing successful laser spot overlapping between adjacent molten tracks. To investigate the defect formation mechanisms, this work establishes a double-track multi-scale phase transition-multiphysics coupled model for diamond/CuSn20 composites. Through integrated CFD-based numerical simulation and experimental approaches, the effects of hatch spacings variations on molten pool evolution, defect generation mechanisms, and mechanical properties of diamond-metal composites were investigated. The principal findings are as follows: (1) Residual temperature from the first molten track modifies the initial temperature of the second molten track. Simultaneously, the temperature gradient generated by the second laser pass induces remelting of the overlapping. (2) At reduced hatch spacing, thermal damage preferentially occurs in diamond grits, whereas enlarged hatch spacings promote pore formation, unmelted zones, and interfacial gaps in overlapping regions. (3) Specimens fabricated at an 80 μm hatch spacing exhibit the highest compressive strength. Although their COF initially exceeds that of 100 μm-spaced specimens, it decreases below the latter's COF after 14 min of testing. This work provides a systematic analysis of diamond migration behavior and molten pool defect genesis during melting-solidification processes.